Essential components from plant source oils: a review on extraction, detection, identification, and quantification - Rahim, Muhammad Abdul (2023)
Oils derived from plant sources, mainly fixed oils from seeds and essential oil from other parts of the plant, are gaining interest as they are the rich source of beneficial compounds that possess potential applications in different industries due to their preventive and therapeutic actions. The essential oils are used in food, medicine, cosmetics, and agriculture industries as they possess antimicrobial, anticarcinogenic, anti-inflammatory and immunomodulatory properties. Plant based oils contain polyphenols, phytochemicals, and bioactive compounds which show high antioxidant activity. The extractions of these oils are a crucial step in terms of the yield and quality attributes of plant oils. This review paper outlines the different modern extraction techniques used for the extraction of different seed oils, including microwave-assisted extraction (MAE), pressurized liquid extraction (PLE), cold-pressed extraction (CPE), ultrasound-assisted extraction (UAE), supercritical-fluid extraction (SFE), enzyme-assisted extraction (EAE), and pulsed electric field-assisted extraction (PEF). For the identification and quantification of essential and bioactive compounds present in seed oils, different modern techniques—such as high-performance liquid chromatography (HPLC), gas chromatography–mass spectrometry (GC-MS), Fourier transform infrared spectroscopy (FTIR), gas chromatography–infrared spectroscopy (GC-IR), atomic fluorescence spectroscopy (AFS), and electron microscopy (EM)—are highlighted in this review along with the beneficial effects of these essential components in different in vivo and in vitro studies and in different applications. The primary goal of this research article is to pique the attention of researchers towards the different sources, potential uses and applications of oils in different industries.